"You chaps mustn't worry when you come back" : Cape Town soldiers and aspects of the experience of war and demobilisation 1939-1953 - Greenbank, Kevin; Greenbank, Kevin (Department of Historical Studies, 2017)
Very little scholarly work has been written about Cape Town during the Second World War. Indeed, very little has been written about South African society at all during this period. This study is an attempt to contribute towards scholarly discussion of the effects of war on South African society, and to try to understand the largely neglected effects of the War on those who took part in it. Much of this study focuses on the experiences of white Englishspeaking veterans. This is because the majority of soldiers fighting in the Second World War were from this particular population group, and also because it was this group that was about to lose commanding political influence upon its return to South Africa. A central theme of this study is the government's neglect of the returning soldiers, and their failure to live up to their promises. The change of government in 1948 was to ensure that the needs of the ex-volunteers were never fully addressed, and that the veterans would never occupy the central position in society which they thought was their right, having fought in a war which many members of the new government had opposed. The focus on Cape Town also ensures that this study remains separate from the many papers which have been written detailing the rise of Nationalism from the late 1930s until the 1948 election. Looking at the other side of the political spectrum - at the eventual losers - has important and interesting political and historical implications, and adds a new dimension to the political history of the period. The methodology used for this study is mainly oral - interviews were conducted with a small representative sample of veterans and have provided a basis for all secondary research. Using the testimony of veterans has proved a useful and original tool for examining the period in question. One further aim of the thesis is to provide an opportunity for the voices of the veterans to be recognised as an authoritative resource about the history of Cape Town during the War and in the immediate post-War period. The thesis is split into two parts to reflect the different nature of Cape Town society during and after the War. The early part deals with Cape Town during the War and the changes which were taking place there as a result of South African participation in the conflict. This section also examines the wartime experiences of the soldiers and assesses how these experiences helped to forge new identities and behaviour after the War. Part Two looks at the post-War period and the demobilisation process, examining how it treated and prejudiced the soldiers who were involved.